Incidence of four canals in root-canal-treated mandibular first molars in Bangladeshi population - Khan, Atiquzzaman; Ahmed, Rubaba; Chowdhury, Shirin Sultana; Qauder, SM Abdul (Update Dental College Journal, 2015)
The aim of this in-vivo study was to assess the incidence of four root canals in clinical cases of root-treated mandibular first molars in Bangladeshi population. A clinical study of 135 root canal treated permanent mandibular first molars was conducted. The teeth were examined clinically and radiographically. The results showed that 52.59% of the examined teeth had three root canals (two mesial and one distal), 45.92% had four root canals (two mesial and two distal) and 0.0148% had five root canals (three mesial and two distal). All the teeth had two roots and no three rooted mandibular first molar found. So it can be concluded that the occurrence of three root canals in mandibular first molar is higher but four root canals is also high in Bangladeshi population. Update Dent. Coll. j: 2014; 4 (2): 04-08